RADIATION DEGRADATION OF PCBS IN SEDIMENTS: COMPARISON OF TWO METHODS - Ľubica Darážová; Andrea Šagátová; Vladimír Nečas; Marko Fülöp; Bumsoo Han (Acta Polytechnica CTU Proceedings)
Polychlorinated biphenyls are toxic compounds which have accumulated in river sediments in Eastern Slovakia. Bioaccumulation could cause even cancer. Radiation degradation with electrons is new and perspective method to dechlorinate PCBs in sediment matrix. We tested the influence of two difference chemical pretreatments and electron irradiation on PCB contaminated sediments.